POTRET KESEHATAN MASYARAKAT DI KOTA PADANG DENGAN METODE WAJAH CHERNOFF - Oktavia, A; Rina, I; Agusta, V (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2019)
Chernoff Face Method is a method used to represent multiple variable data in the form of a cartoon face with 20 specific facial features. In this study, we will show how the use of the Chernoff face method to see a portrait of public health in the city of Padang. Health indicators will be paired with specific facial features of Chernoff's face using Principal Component Analysis (PCA). The results of this study are expected to provide an overview of public health protection for each sub-district in Padang City and Padang City as a whole. Keywords : Chernoff Face Method, Health Indicators, Principal Component Ananlysis.